2002
DOI: 10.1111/j.1542-474x.2002.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Nervous System Influences on the Induction of Ventricular Tachycardia

Abstract: Among patients preselected for exercise-induced ventricular tachycardia, almost half could be induced into ventricular tachycardia by isoproterenol infusion. Mental stress was a less powerful inducer of ventricular arrhythmias in this study group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Several studies 6,19,21,22 have suggested that changes in adrenergic tone are involved in the genesis and maintenance of cardiac arrhythmias, including potentially life‐threatening arrhythmias, and that the use of beta‐blocking medication plays an important role as an anti‐arrhythmic 23 . However, our results showed that most arrhythmias observed during CPET occurred in the group already using beta‐blockers.…”
Section: Discussioncontrasting
confidence: 68%
“…Several studies 6,19,21,22 have suggested that changes in adrenergic tone are involved in the genesis and maintenance of cardiac arrhythmias, including potentially life‐threatening arrhythmias, and that the use of beta‐blocking medication plays an important role as an anti‐arrhythmic 23 . However, our results showed that most arrhythmias observed during CPET occurred in the group already using beta‐blockers.…”
Section: Discussioncontrasting
confidence: 68%
“…In addition, SVT can have multiple sites of origin, making the task of eliminating all circuits a challenge 201,207,213,229,230 . In general, the site of origin of well-tolerated recurring SVT can be identified and the SVT interrupted in 60%-80% of the patients, but rapid and poorly tolerated SVT are frequently induced in the final assessment of the procedure 201,213,[227][228][229] . During long-term follow-up, at least 50% of the patients undergoing conventional ablation have clinical relapse, justifying the maintenance of antiarrhythmic drugs or ICD implantation 230 .…”
Section: Catheter Ablation Of Svt In CCCmentioning
confidence: 99%
“…Most arrhythmias and conduction disorders occur during the chronic phase, being direct consequences of the chronic fibrosing myocarditis triggered by T. cruzi 28,198 , with formation of scars and aneurysms 24,28,198 . Those myocardial scars, focal or scattered spread across the ventricles, contribute to the genesis of reentry ventricular arrhythmias [199][200][201] . In addition, the cardiac excito-conduction tissue is frequently damaged, leading to sinus node dysfunction and disorders of the atrioventricular and intraventricular conduction 28,198 .…”
Section: Latin American Guideline For the Diagnosis And Treatment Omentioning
confidence: 99%
See 2 more Smart Citations